The Effect Of Special Exercises Using Teaching Aids on Some Basic Skills In Volleyball For First Year Secondary School Students - Khammas, Raad; Sabhan, Hussein (Journal of Physical Education, 2019)
Using virtual reality glasses along with other updated technology in learning has a great role in developing fundamental skills in first year secondary school students. The researchers found a weakness in learning and lack of attention to learning fundamental skills in volleyball. The researchers used the descriptive method on (3200) students from Baghdad Education Bureau for the academic year 2018 – 2019.  The teaching program consisted of (8) weeks applied on (10) first year secondary school students. The data was collected and treated proper statistical operations to conclude that there is a positive development in overhead and underarm passing special exercises in volleyball. Finally the researchers recommended the necessity of making similar studies on other variables.